2005
DOI: 10.1207/s15327655jchn2202_4
|View full text |Cite
|
Sign up to set email alerts
|

Orphan Care in Malawi: Current Practices

Abstract: HIV and AIDS has moved rapidly throughout sub-Saharan Africa, dramatically adding to the crisis of orphaned children on the continent. Knowledge of African responses to their problem is needed so that interventions from the global community are culturally appropriate. An assessment of 73 programs caring for over 100,000 vulnerable and orphaned children in Malawi was conducted. A cross section of programs throughout the country was visited. Three primary care strategies were found: community-based orphan care, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 1 publication
1
32
0
Order By: Relevance
“…There are many different models of orphan care, three of which are communitybased, institutional residential care and self-care (Beard, 2005). The official policy in Malawi is that the extended family, caring the orphan within the community is the preferable form.…”
Section: Discussionmentioning
confidence: 99%
“…There are many different models of orphan care, three of which are communitybased, institutional residential care and self-care (Beard, 2005). The official policy in Malawi is that the extended family, caring the orphan within the community is the preferable form.…”
Section: Discussionmentioning
confidence: 99%
“…They might, for example, have a particularly good relationship with their foster-carers; in the Malawian case, these might be orphans that were left in a better financial position by their biological parents, or perhaps have benefited from programmes aimed at orphans and vulnerable children while others have not (see Beard, 2005). Unfortunately, data limitations preclude going beyond speculation here, but this would be worth pursuing in further research.…”
Section: Context Matters: Understanding the Variation In Outcomes Betmentioning
confidence: 98%
“…This finding is not only consistent with prior research but adds to argument for consistently using PSWCHW in programming service delivery for vulnerable children. This finding helps support communitybased health care research that has shown PSWCHW help to address a wide range of issues for the vulnerable population, from psychosocial support to adherence to HIV treatment for the population they serve (Pegurri et al, 2015;Taylor & Kvalsvig, 2008) PSWCHW were able to address issues of adherence to health care and to provide supportive mental health interventions, sexual health education, and ways to navigate cultural social spheres to ensure community needs were served (Beard, 2005;Friedman, 2005;Hermann et al, 2009;Pegurri et al, 2015). Their community knowledge helped them use individuals' and family strength to assist them (Heath et al, 2008).…”
Section: Discussionmentioning
confidence: 58%
“…Clinical adherence, mental health, sexual health and social spheres must be included in the provision of care for children living with HIV (Pegurri et al, 2015). Social work and public health care intersect when supporting households at the community level (Beard, 2005;Friedman, 2005;Hermann et al, 2009). Evidencebased interventions strengthen resilience among OVC (Heath, Donald, Theron, & Lyon, 2008).…”
Section: Para-professionals In Practice and Implications For Social Wmentioning
confidence: 99%